Impact of Polypyrrole Functionalization on the Anodic Performance of Boron Nitride Nanosheets: Insights From First-Principles Calculations - Nnadiekwe, Chidera C.; Abdulazeez, Ismail; Haroon, Muhammad; Peng, Qing; Jalilov, Almaz; Al-Saadi, Abdulaziz (Frontiers in Chemistry, 2021)
Lithium-ion batteries (LIBs) have displayed superior performance compared to other types of rechargeable batteries. However, the depleting lithium mineral reserve might be the most discouraging setback for the LIBs' technological advancements. Alternative materials are thus desirable to salvage these limitations. Herein, we have investigated using first-principles DFT simulations the role of polypyrrole, PP functionalization in improving the anodic performance of boron nitride nanosheet, BNNS-based lithium-ion batteries and extended the same to sodium, beryllium, and magnesium ion batteries. The HOMO-LUMO energy states were stabilized by the PP functional unit, resulting in a significantly reduced energy gap of the BNNS by 45%, improved electronic properties, and cell reaction kinetics. The cell voltage, ΔEcell was predicted to improve upon functionalization with PP, especially for Li-ion (from 1.55 V to 2.06 V) and Na-ion (from 1.03 V to 1.37 V), the trend of which revealed the influence of the size and the charge on the metal ions in promoting the energy efficiency of the batteries. The present study provides an insight into the role of conducting polymers in improving the energy efficiency of metal-ion batteries and could pave the way for the effective design of highly efficient energy storage materials.